PERTANGGUNG JAWABAN PEJABAT PEMERINTAH AKIBAT TERJADINYA MALADMINISTRASI DALAM PELAYANAN PUBLIK - Ryo Martin Sopian; Annisha Amalia, Zainab Ompu Jainah (ADISAM PUBLISHER, 2024)
The concept of a welfare state upholds the existence of a legal system that guarantees legal certainty and protection of the basic rights of the people. This is in line with the Preamble to the 1945 Constitution paragraph IV which states: